The potential for an agroecological approach in Scotland: policy brief - Cole, Lorna J; Holland, John P; Eory, Vera; Karley, Alison J; Hawes, Cathy; Walker, Robin L; Watson, Christine A (Scotland’s Rural College, 2022)
Agroecology is receiving increasing attention for its potential to reconcile environmental, sustainability and food production goals, through restoring the health of agricultural ecosystems and increasing the resilience of farms to future challenges. This study examined five different agroecological approaches that are currently practiced in Scotland to determine their potential to support the delivery of policy targets relating to climate change, biodiversity, and food production.
Keywords: agroecology; resilience; climate change; agroforestry; low input; organic; integrated; regenerative